The Mediating Effect of Brand Equity on Purchase Intention in E-commerce: The Role of E-WOM, Social Media Market-ing, Brand Image, and Knowledge - Fendy Cuandra; Justin Justin; Isnaini Nuzula Agustin; Lily Purwianti; Stefhani Susanto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study discusses the mediating role of brand equity variables on the relationship between electronic word of mouth, social media marketing, brand image, and brand knowledge variables on purchase intention in the context of e-commerce platforms. This study utilizes smart pls 3 to analyze 384 data that have been collected through google form. There are results from the study in the form of the mediating effect of brand equity on electronic word of mouth and social media marketing on purchase intention does not provide a significant influence, but electronic word of mouth, social media marketing, brand image, and brand knowledge have a significant influence on brand equity which will then provide a significant influence on purchase intention from brand equity. This study adopts the theory of planned behavior as the grand theory to discuss these variables which makes this study novelty. In order to remain competitive within the e-commerce industry, businesses must enhance electronic word of mouth, social media marketing, brand image, and brand knowledge. These efforts play a role in enhancing brand equity, which in turn influences consumer attitudes and habits, resulting to increased purchase intention and shopping activity on the e-commerce platform.